Animality and Colonial Subjecthood in Africa : The Human and Nonhuman Creatures of Nigeria - Aderinto, Saheed (Book collections on Project MUSE., 2022)
"From debates over the aesthetics of birds in the urban landscape to how horse racing enhanced imperial power to the ways in which water navigation impacts aquatic creatures, Saheed Aderinto argues that it is impossible to comprehend the full extent of imperial domination without considering the colonial subjecthood of animals"--